Dampak Pembatalan Syarat Sertifikat Pelatihan Untuk Pengangkatan Jabatan Notaris Berdasarkan Hukum di Indonesia - Natasya, Angel Olivia; Hosein, Siti Hajati (AL-MANHAJ: Jurnal Hukum dan Pranata Sosial Islam, 2023)
After the Supreme Court Decision, Number 50 P / HUM / 2018 concerning the Cancellation of Permenkumham Number 62 of 2016 concerning Terms and Procedures for Appointment, Transfer, Dismissal, and Extension of Notary Term of Office, which is considered contrary to Article 3 of Law Number 2 of 2014 concerning Amendments to Law Number 30 of 2004 concerning the Position of Notary has an impact, namely the issuance of Permenkumham Number 19 of 2019. Permenkumham Number 19 of 2019 changed the notary appointment examination as one of the conditions for the appointment of the position of Notary to the required photocopy of the training certificate for improving the quality of the Notary position. The cancellation of the Permenkumham was then repeated with the Supreme Court Decision No. 3 P/HUM/2022 which invalidated Article 2 paragraph (3) of Permenkumham No. 19 of 2019, which was deemed detrimental by the Petitioner in this case because of the long, long-winded and costly process. This research is expected to provide explanations and solutions to the above problems carried out using normative juridical methods guided by applicable laws and regulations.